E-health Literacy and Older Adults: Challenges, Opportunities, and Support Needs - Saadati, Nadereh; Yousefi, Zahra; Saadati, Seyed Alireza (AI and Tech in Behavioral and Social Sciences, 2023)
This study aimed to explore the challenges, opportunities, and support needs related to e-health literacy among older adults. By identifying these key areas, the study seeks to inform the development of targeted interventions and resources to enhance e-health literacy within this demographic. A qualitative research design was employed, involving semi-structured interviews with 16 older adults who have interacted with e-health platforms in the past year. Participants were purposively selected to ensure a diverse range of experiences. Data were analyzed using thematic analysis to identify major and minor themes related to e-health literacy challenges, opportunities, and support needs. The analysis revealed three major themes: Challenges, Opportunities, and Support Needs. Under Challenges, participants identified Technological Barriers, Health Literacy Issues, Accessibility Concerns, and Privacy and Security Fears. Opportunities highlighted were Enhanced Access to Health Information, Improved Patient-Provider Communication, and Personal Health Management. For Support Needs, the study found a demand for Educational Programs, Technical Assistance, and Customizable E-Health Tools. These findings underscore the multifaceted nature of e-health literacy among older adults and the need for comprehensive support mechanisms. Older adults face significant barriers to fully leveraging e-health resources, yet there exist substantial opportunities to enhance their e-health literacy through targeted support and interventions. Addressing the identified challenges and support needs can lead to improved health outcomes for older adults by facilitating more effective use of digital health platforms. The study underscores the importance of developing tailored e-health literacy resources that consider the unique circumstances and preferences of older adults.